PELATIHAN DAN PENDAMPINGAN PETANI DALAM PENGGUNAAN PGPR UNTUK BUDIDAYA TANAMAN HORTIKULTURA DI DESA BINTURU KECAMATAN KELUA KABUPATEN TABALONG, KALIMANTAN SELATAN - Sepe, Muslimin; Rosa, Helda Orbani; Marsuni, Yusriadi; Hariyadi, Nursyifa Nada; Naufal, Muhammad (BAKIRA: Jurnal Pengabdian Kepada Masyarakat, 2024)
Plant Growth Promoting Rhizobacteria, or PGPRs, are a type of bacteria that live in rhizospheres, or the areas of land near tomato plants. These bacteria can cause a variety of processes, such as the formation of nitrogen, the breakdown of fat, the synthesis of phytohormones, and the development of illnesses. The purpose of this nirlaba service is to provide information and resources that are required for pet owners and pertanian owners in order to produce and use PGPR locally and effectively. This is expected to improve tuna quality, increase tuna health, and result in more efficient use of pupuk. The training's outcome indicates that participants can create and use PGPR on their own effectively, increasing textile production on a global scale. This training also emphasizes the importance of environmental sustainability and resiliency through the use of PGPR agents.